2017
DOI: 10.1038/s41598-017-09187-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-time EEG-based brain-computer interface to a virtual avatar enhances cortical involvement in human treadmill walking

Abstract: Recent advances in non-invasive brain-computer interface (BCI) technologies have shown the feasibility of neural decoding for both users’ gait intent and continuous kinematics. However, the dynamics of cortical involvement in human upright walking with a closed-loop BCI has not been investigated. This study aims to investigate the changes of cortical involvement in human treadmill walking with and without BCI control of a walking avatar. Source localization revealed significant differences in cortical network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 62 publications
1
87
0
Order By: Relevance
“…At the same time, lower alpha activity over widespread areas of the scalp (from frontal to parietal cortex, and in some cases over the whole scalp) has also been observed when walking as compared to standing or resting (Beurskens et al, 2016;Peterson & Ferris, 2018). In addition, a decreased alpha power was observed when performing cognitively engaging tasks such as walking in an interactive virtual environment (Wagner et al, 2014) and closed-loop brain-computer interface (BCI) control of a virtual avatar walking (Luu et al, 2017).…”
Section: Psds Of CMI During Walkingmentioning
confidence: 99%
“…At the same time, lower alpha activity over widespread areas of the scalp (from frontal to parietal cortex, and in some cases over the whole scalp) has also been observed when walking as compared to standing or resting (Beurskens et al, 2016;Peterson & Ferris, 2018). In addition, a decreased alpha power was observed when performing cognitively engaging tasks such as walking in an interactive virtual environment (Wagner et al, 2014) and closed-loop brain-computer interface (BCI) control of a virtual avatar walking (Luu et al, 2017).…”
Section: Psds Of CMI During Walkingmentioning
confidence: 99%
“…By contrast, BMI approaches directly measures brain activity to control robotic devices, therefore encourage neural activities that drive the designated motor tasks. These approaches encourage voluntary control and motor intent from users, which have been demonstrated as one of the main principles in rehabilitation and may trigger stronger neuroplasticity (Koenig et al 2011, Luu et al 2017. Additionally, better understanding of neural representations of human movements from advanced BMI technology may propel the development of a novel training paradigm for improving the efficacy of rehabilitation in a top-down approach.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Among the identified studies, (He et al 2014) reconstructed the joint angles and electromyography (EMG) envelopes of lower limbs of the subjects in an offline analysis. The method was later adapted to control a virtual avatar on a screen in realtime (Luu et al 2017). Vouga et al (2017) demonstrated a realtime BMI for a monkey exoskeleton.…”
Section: Output From the Brain-machine Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The decoding of this brain activity is a necessary step to build valid brain-computer interfaces (BCIs) able to generate gait artificially [85]. As a perspective, a real-time closed-loop BCI that decodes lower limb joint angles from scalp EEG during treadmill walking in order to control the walking movements of a virtual avatar has already been built [86]. This kind of approach could be useful in rehabilitation programs since healthy subjects are able to adapt an avatar's gait pattern controlled via a closed-loop EEG-based BCI in eight days of training.…”
Section: Discussionmentioning
confidence: 99%